Manajemen Pengembangan Karakter Peserta Didik Berbasis Kegiatan Ekstrakurikuler - Hidayat Hidayat (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
This research aims to describe the management of extracurricular activities based on student character development. The research uses qualitative descriptive methods. The research subjects were the principal, deputy principal, teachers and students. Data collection techniques were carried out using observation, interviews and documentation. Data analysis is carried out using data collection, data reduction, data presentation, inference and/or verification techniques. The research results show that student character development is based on extracurricular activities that have been implemented based on effective management principles which include planning, organizing, implementing, monitoring and evaluating processes. Of the many extra-curricular activities, the Tahfzih Qur'an extra activity is the favorite activity of Al Rasyid Islamic Elementary School, Pekanbaru, as well as becoming an icon and characteristic and even a source of pride for the entire school community which is celebrated through the tahfizh graduation every year at well-known hotels in Pekanbaru.